(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
Employment or right to work of persons with disabilities is the last stage of the long and complex process of their rehabilitation. In professional theory of special education employment is the last stage of integrating these persons in the community. According to information at its disposal which Community trade in protective association in year 2011 Republic of Macedonia has: - 411 trade association which employed 3541 persons with disabilities from which 3350 are disabled of all categories and 191 are working disabled; - 406persons working as sole proprietor or working with sole traders; - 971 disabled persons working in trade companies with open economy; - 15 disabled persons working in the public sector or total of 5339 persons with disabilities worked in year 2011. In article, 19 paragraph 3 of the Law of labor relations of Republic of Macedonia is established: “Person with disabilities who is capable to work certain things is consider with ability of health for closure of labor contract for those certain things The same Law prohibits discrimination of the employment candidate respectively labor with disabilities and provides lawsuit for compensation of damage due to discrimination on the basis of disabilities and load proof that there was not discrimination falls to the employer. From this we can concluded that in Macedonia, protection of persons with disabilities in the area of employment is conducting not though assigning certain protective groups of persons with disabilities but through the system of antidiscrimination.